A proposed model for early warning broadcast landslide in Peru using digital terrestrial television - Rosales H., Jimmy (2015)
With the implementation of Digital Terrestrial Television (DTT) in Latin American countries and their ability to develop interactive services, it opens a new way to enhance existing applications that allow connectivity using ubiquitous communication. Peru is a country located in the Ring of Fire and has many natural disasters constantly being prone to landslides. Therefore, in the present work it is to use DTT to help people in the event of a natural disaster through early warning, as a message that will appear on a TV monitor as a window informing about the situation, this information is important as it provides communication alert in emergency situations and is vital to reduce the number of victims could be produced. The purpose of this paper is to propose a model of early warning in case of occurrence of a landslide (landslide), which could be applied in the future in some of these natural events prone areas. This model proposes its relevance to the Peruvian reality and serves as a starting point for using DTT in the case of other similar emergency.